Person-Job Fit, personality, organizational commitment and intention to stay among employees in marketing departments - Goh, Ee Leng; Lee, Michelle Chin Chin (Penerbit Universiti Kebangsaan Malaysia, 2016)
The current study utilized a cross-sectional method among 153 employees in various marketing departments in Malaysia to investigate the influence of personality factors (i.e. extraversion and agreeableness) on person-job fit (P-J fit) and organizational commitment. It is hypothesized that organizational commitment mediates the relationship between P-J fit and intention to stay, and personality factors interact with P-J fit on organization commitment. Results showed that there were significant relationships between P-J fit, organizational commitment, and intention to stay. Both personality factors showed differences in one’s organizational commitment and intention to stay. The study highlighted the importance of fit and personality of an individual in a marketing department. Personality test is suggested to continue to be used as one of the assessment tools during hiring process for marketing department as it helps to select candidates whose personality is suitable for the job.